HYPOTHESIS TESTS ON HALL PERMANENT INCOME (HPI): THE CASE OF INDONESIA - R. Maryatmo (Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
This paper is focused on the test of Hall Permanent Hypothesis. Hall hypothesizes that economic agents have perfect information on their life time income. Since economic agents have perfect information on their life time income, they tend to hold their inter-temporal consumption to be equal. There are three ways to test the Hall hypothesis. The three ways are Dickey Fuller, Augmented Dickey Fuller, Cambell and Mankiw tests. The results are inconsistent each others. The finding tends to support that the interest rate transmission mechanism for inter-temporal consumption is not working in Indonesia. The interest rate in Indonesia tends to be higher than of the neighboring countries. The interest rate in Indonesia tends to be high because of the high inflation rate, and inefficient banking practice. It is interesting to plan further research on staggering high inflation and inefficient banking practice in Indonesia.Keywords: Hall income permanent hypothesis, inflation, Indonesia.